Interval between secondary cytoreductive surgery and adjuvant chemotherapy is not associated with survivals in patients with recurrent ovarian cancer - Soo Young Jeong; Chel Hun Choi; Tae Joong Kim; Jeong Won Lee; Byoung-Gie Kim; Duk Soo Bae; Yoo-Young Lee (Journal of Ovarian Research, 2019)
Abstract Background Secondary cytoreductive surgery (SCS) is possible in selected patients with recurrent epithelial ovarian cancer (EOC). The goal of SCS is complete resection, although chemotherapy is always followed. Delayed intervals between primary debulking surgery and adjuvant chemotherapy was reported to be associated with poorer survivals, however, the role of intervals in recurrent disease is still unknown. Materials and methods This retrospective cohort study reviewed data from electronic medical records of women with recurrent EOC treated at Samsung Medical Centre, Seoul, Korea, between January 1, 2002, and December 31, 2015. Patients who underwent SCS with adjuvant chemotherapy for recurrent EOC were eligible. We defined intervals as the period between the day of SCS and the first cycle of adjuvant chemotherapy. Results Seventy-nine patients were eligible for this study. Their median age was 48 (range, 18–69) years and median interval between the date of SCS and initiation of adjuvant chemotherapy was 10 (range, 4–115) days. The rate of complete resection was 72.2% (57/79). Division of the patients by interval (Group 1, interval ≤ 10 days; Group 2, interval > 10 days) revealed no difference in clinical parameters. No gross residual disease after SCS (no vs. any gross residual, p = 0.002) and longer platinum-free survival (over 12 vs. 6–12 months, p = 0.023) were independent favorable prognostic factors in Cox model; however, the intervals did not affect survival. Conclusions Delayed intervals to adjuvant chemotherapy after secondary cytoreductive surgery is not associated with decreased survivals. It is important to identify recurrent EOC patients who might have no gross residual disease following SCS. Moreover, surgeons should strive for complete resection.